Changes in postural control after inducing fatigue in junior sailors wearing compression garments - Welman, K. E.; Walker, C. N.; Chamberlain, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Balance is one of the critical factors that affects athletes` performances, and is recognized to have a central role in sport injury prevention. Fatigue deteriorates postural and neuromuscular control, which increases the injury risk (Paillard, 2012). Compression garments (CG) have been shown to improve fatigue and recovery, thereby indirectly benefiting performance. It is not known if this is true for sailors and in particular young individuals with poorer postural control (PC). The study endeavour to determine if lower body CG influences elite junior sailors` PC after a fatigue-inducing protocol. Methods: Nine healthy elite sailors (Age: 13 ± 1 years; BMI: 20 ± 3 kg/m²; Professional Sailing: 3 ± 1 years) volunteered for the study. Each participant acted as their own control and randomly completed the trials without (CON) or with CG. Participants were subjected to a maximum incremental hiking fatiguing protocol (HFP) developed by Blackburn (2000). The effects on counter movement jump (CMJ) variables (jump height, power, force and velocity), lactate (LT) and postural sway (PS) variables were analysed pre- and post-HFP. Results: Generally the sailors took 7±2 minutes to fatigue, with a weight of 21±4 kg. No differences were observed between the two HFP in Time to Fatigue (p=0.36) and Weight Held at Fatigue (p=0.41). CMJ performances showed a 12% and 3% reduction in jump height for CON and CG, respectively (p=0.15; d=0.76). Jump power after fatigue increased by 11% in the CG trial (p=0.06; d=1.01). Decreased jump velocity in CON trial was observed (p=0.09; d=0.91) with a plateau in CG (p=0.65; d=0.23). PS variables deteriorated in the CON trials (p<0.05), whereas overall PS improved while wearing CG (p=0.04). Directly after the HFP LT was significantly lower (p=0.04; d=1.17) in CG trial compared to CON (4±2 vs. 10±7 mmol/L, respectively). Discussion: The results for the performance variables seem to correspond to the improvements in PS variables. This suggests that CG may have reduced the fatigue experienced by sailors while quasi-isometric stress was placed on the quadriceps muscles. Sailors can prolong endurance time in the hiking position by adjusting neural activity distribution among synergists, thereby minimizing the contribution of the most fatigable muscles (CuévelJ, 2006). CG may have improved proprioceptive feedback and, together with less fatigue, this lead to improved PS. Better PC means reduced risk for injuries and more accurate movements during fatiguing activities.